Let's (not) get together!: The role of social norms in social distancing during COVID-19 - Deborah Martinez; Cristina Parilli; Carlos G. Scartascini; Alberto Simpser (Inter-American Development Bank (IDB), 2021)
While effective preventive measures against COVID-19 are now widely known, many individuals fail to adopt them. This paper provides experimental evidence about one potentially important driver of compliance with social distancing: social norms. We asked each of 23,000 survey respondents in Mexico to predict how a fictional person would behave when faced with the choice about whether or not to attend a friend's birthday gathering. Every respondent was randomly assigned to one of four social norms conditions. Expecting that other people would attend the gathering and/or believing that other people approved of attending the gathering both increased the predicted probability that the fictional character would attend the gathering by 25% in comparison with a scenario where other people were not expected to attend nor to approve of attending. Our results speak to the potential effects of communication campaigns and media coverage of, compliance with, and normative views about COVID-19 preventive measures. They also suggest that policies aimed at modifying social norms or making existing ones salient could impact compliance.
Keywords: D91; D90; I12; I18; 330; COVID19; Social norms; Social distancing; Normative expectations; Empirical expectations; Compliance